A gap in the planetesimal disc around HD 107146 and asymmetric warm dust emission revealed by ALMA. Issue 4 (5th July 2018) - Marino, S; Carpenter, J; Wyatt, M C; Booth, M; Casassus, S; Faramaz, V; Guzman, V; Hughes, A M; Isella, A; Kennedy, G M; Matrà, L; Ricci, L; et al.
ABSTRACT: While detecting low-mass exoplanets at tens of au is beyond current instrumentation, debris discs provide a unique opportunity to study the outer regions of planetary systems. Here, we report new ALMA observations of the 80–200 Myr old Solar analogue HD 107146 that reveal the radial structure of its exo-Kuiper belt at wavelengths of 1.1 and 0.86 mm. We find that the planetesimal disc is broad, extending from 40 to 140 au, and it is characterized by a circular gap extending from 60 to 100 au in which the continuum emission drops by about 50 per cent. We also report the non-detection of the CO J = 3–2 emission line, confirming that there is not enough gas to affect the dust distribution. To date, HD 107146 is the only gas-poor system showing multiple rings in the distribution of millimetre sized particles. These rings suggest a similar distribution of the planetesimals producing small dust grains that could be explained invoking the presence of one or more perturbing planets. Because the disc appears axisymmetric, such planets should be on circular orbits. By comparing N -body simulations with the observed visibilities we find that to explain the radial extent and depth of the gap, it would require the presence of multiple low-mass planets or a single planet that migrated through the disc. Interior to HD 107146's exo-Kuiper belt we find extended emission with a peak at ∼20 au and consistent with the inner warm belt that was previously predicted based on 22 μ m excess as in many other systems. This warm belt is the first to be imaged, although unexpectedly suggesting that it is asymmetric. This could be due to a large belt eccentricity or due to clumpy structure produced by resonant trapping with an additional inner planet.